Produção de material didático acessível para surdos no moodle - Cureau, Mara Rúbia Roos (2017)
The inclusion of deaf students in higher education is a reality at the Federal University of Santa Maria (UFSM). With this, the use of the Virtual Environment of Teaching and Learning (AVEA) MOODLE by the instution has brought some challenges, both for teachers and deaf students. In order to minimize the problems related to the accessibility of MOODLE to students and the need to provide courseware accessible to students and teachers, this study focused on the production of Accessible Learning Material (MDA). The "accessibility of the deaf student on higher education supported by the Virtual Environment of Teaching-Learning (AVEA) Moodle" is made possible through the implementation of moodle.org and is guaranteed by Decree 6.949 / 2009, which guides that the courseware must be made available in the "languages and in the modes and means of communication most appropriate to the individual and in environments that favor the maximum of their academic and social development." Therefore, this research was evaluated as contributions and limits of an Open Discipline (DA), a research product, not AVEA Moodle in relation to the production of MDA for deaf students in the UFSM context. A research supported by a qualitative approach, an exploratory descriptive study with documentary and content analysis that enabled an interpretation of a materialized reality in the access reports of the participants of the research in Moodle’s DA and the analysis of the answers obtained in the questionnaires. An evaluation of DA was performed through online questionnaires about the DA, applied to deaf students, deaf teachers and to hearing teachers. As a result of the DA assessment, deaf and hearing teachers indicated that the visual presentation of DA’s courseware would allow the deaf student to acess the materials from the perspective of universal design. The deaf students, in turn, declared that an MDA production initiative in AVEA was positive. An analysis of the obtained data allowed to create relationships between the adopted literature and the investigated reality, and the deaf students deemed relevant the placement of the images as contextualizers of the texts used in the discipline, however, they had difficulties in visualizing the subtitles through the translator of the VLibras, the deaf teachers mentioned no issues with the use of the Libras translator, as well as the hearing teachers, in the other subjects of the instrument, the evaluation was positive, especially in the contextualization of the images to the texts produced in the DA and also in two columns presentation. The DA presents organizational elements, developed and made available considering the general principles of accessibility for materials in virtual format, aiming, therefore, to contribute to the permanence and success of deaf students in this modality of teaching.